JAK/STAT mediated insulin resistance in muscles is essential for effective immune response - McMullen, Ellen; Strych, Lukas; Chodakova, Lenka; Krebs, Amber; Dolezal, Tomas (Cell communication and signaling, 2024)
BACKGROUND: The metabolically demanding nature of immune response requires nutrients to be preferentially directed towards the immune system at the expense of peripheral tissues. We study the mechanisms by which this metabolic reprograming occurs using the parasitoid infection of Drosophila larvae. To overcome such an immune challenge hemocytes differentiate into lamellocytes, which encapsulate and melanize the parasitoid egg. Hemocytes acquire the energy for this process by expressing JAK/STAT ligands upd2 and upd3, which activates JAK/STAT signaling in muscles and redirects carbohydrates away from muscles in favor of immune cells. METHODS: Immune response of Drosophila larvae was induced by parasitoid wasp infestation. Carbohydrate levels, larval locomotion and gene expression of key proteins were compared between control and infected animals. Efficacy of lamellocyte production and resistance to wasp infection was observed for RNAi and mutant animals. RESULTS: Absence of upd/JAK/STAT signaling leads to an impaired immune response and increased mortality. We demonstrate how JAK/STAT signaling in muscles leads to suppression of insulin signaling through activation of ImpL2, the inhibitor of Drosophila insulin like peptides. CONCLUSIONS: Our findings reveal cross-talk between immune cells and muscles mediates a metabolic shift, redirecting carbohydrates towards immune cells. We emphasize the crucial function of muscles during immune response and show the benefits of insulin resistance as an adaptive mechanism that is necessary for survival.
Keywords: Muscles; transkripční faktory STAT; sršňovití; Janus Kinases; JAK/STAT signaling; Carbohydrates; Insulin Resistance; Transcription Factors; svaly; sacharidy; larva; Immunity; Drosophila Proteins; Janus kinasy; zvířata; Insulin resistance; imunita; Wasps; proteiny Drosophily; Metabolism; inzulinová rezistence; Insulin-Like Growth Factor Binding Proteins; proteiny vázající IGF; Drosophila; Larva; transkripční faktory; Animals; STAT Transcription Factors